The value of PD-L1 immunohistochemical expression in Egyptian urinary bladder carcinoma patients - Eman Mohamed Ahmed Nor; Eman Mohamed Saied; Hanan Alsaeid Alshenawy; Aliaa Atef Shams Eldeen (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate programmed death-ligand 1 immunohistochemical expression in the available variants of urinary bladder carcinoma, and to correlate its expression with the available clinicopathological features. Method: The retrospective study was conducted at the Faculty of Medicine, Kafrelsheikh University, Egypt, from February 2020 to April 2021, and comprised formalin-fixed and paraffin-embedded specimens of urinary bladder carcinoma belonging to patients who had no history of radiotherapy or chemotherapy. Immunohistochemical staining of all cases was done using anti-programmed death-ligand 1 antibody. Data was analysed using SPSS 20. Results: Of the 70 specimens, 58(82.86%) had been obtained through transurethral resection of bladder tumours and 12(17.14%) through radical cystectomy. Also, 53(75.7%) specimens belonged to males and 27(24.3%) to females. The age of the cases ranged 34-83 years, and 59(84.3%) were aged ≥45 years. There were 27(38.6%) noninvasive bladder tumours and 43(61.4%) were infiltrating bladder carcinomas. Positive programmed death-ligand 1 expression was detected in 42(60%) cases. Age, gender and histopathological type were not significantly associated with the expression of programmed death-ligand 1. Conclusions: Programmed death-ligand 1 could be considered a predictive marker for aggressive bladder carcinoma and its immunohistochemical expression may aid in identifying selective patients for targeted immunotherapy. Keywords: Carcinoma, Cell, Urinary bladder, Neoplasms, Antigen, Receptor, Immunotherapy, Muscles.